Teachers' Perceived Readiness Towards Implementing English for Teaching Mathematics and Science - Husin, Nor Azilah (2005)
This research was an attempt to study the readiness of secondary school texherc ir! Sehrxp h hple.wnth,g Teachings for Mathematics and Science. The main objectives of the study were to determine the level of teachers' perceived readiness and validate the Confirmatory Factor Analysis (CFA) model for the four constructs measuring teachers' readiness. There were nine research questions posed in order to achieve the objectives. The research design was a descriptive research and the data were collected using questionnaires. The study followed a survey method which used a multi-stage sampling technique to select 210 form one and two Mathematics and Science teachers. Both descriptive and inferential statistics were used to analyze the data of the study.The results of this study had thrown light on teachers' perceived readiness in implementing the new educational reform. It appeared all of the respondents had perceived moderate to high level of overall teachers' readiness. A majority of them had high perception .level in attitude, and content knowledge. A majority of them had a moderate perception level in Information and Communication Technology (ICT) skills and English Language skills. None of the respondents was at low perception level except for the (ICT) skills construct. This result gives a scenario that though the respondents seemed to have perceived the right attitude, sufficient English Language proficiency, and high content knowledge for implementing ETeMS, they were still lacking in ICT skills especially in the web-based activitiest for emfile m d i n-d rpaiving Q-~T&, surfkg the internet and chatting and the utilization of software. For the demographic variables, it was found that school localrty, subject taught, gender, ethnic groups, professionall academic qualifications and training did not have any significant differences in the overall teachers' readiness except the age groups. The younger group, respondents' age 25 to 30 years old perceived that they performed the highest in the ICT skills and overall teachers' readiness among the older groups. There are statistical significant differences in ethnic groups: The Malay teachers show the highest perception in new technology and ICT. The Indian teachers are the most proficient in perceived English Language skills and the Chinese perceived themselves as the most knowledgeable towards the implementation of ETeMS. Three indices were used to examine the goodness-of-fit of the proposed model: (a) the Chi-square (CMINIDF); (b) baseline comparisons: Bentler- Bonnett Normed-Fit lndex (NFI), Incremental Fit lndex (IF]) and Comparative Fit lndex (CFI); and (c) the Root Mean Square Error of Approximation (RMSEA). The data had demonstrated that the model was an acceptable model with 2 < (CMINIDF) < 5, IF1 and CFI > .90 (Bentler & Bonnet, 1980), and RMSEA < 1.0 and data significantly to support the model.